Endowing Conductive Polyetheretherketone/Graphene Nanocomposite with Bioactive and Antibacterial Coating through Electrophoresis. Issue 2 (28th October 2021) - Du, Meixuan; He, Miaomiao; Zhu, Ce; Liu, Zheng; Jiang, Yulin; Zhuang, Yi; Li, Yubao; Feng, Ganjun; Liu, Limin; Zhang, Li
Abstract: Polyetheretherketone (PEEK) and its composites have been widely used in orthopedics and trauma. In this work, a bioactive calcium carbonate (CaCO3 ) coating incorporated with silver nanoparticles (AgNPs) is coated on the conductive PEEK/graphene nanocomposite (P/G) through electrophoretic deposition (EPD) by pumping CO2 to provide tiny amount of CO3 2− groups for reacting with Ca 2+, the obtained sample is named as Ca/Ag@P/G. The morphology, structure, and surface chemistry of the fabricated Ca/Ag@P/G are characterized by means of SEM‐EDS, XRD, XPS, as well as water contact angle testing, and the results confirm that the mixture coating composed of CaCO3 and AgNPs is less crystalline and more hydrophilic than the single CaCO3 coating on P/G (namely Ca@P/G). The Ca/Ag@P/G exhibits desirable antibacterial ability against both S. aureus and E. coli with the bactericidal rate of 99.9% and 96.7%, respectively, meanwhile it displays excellent biocompatibility with improved cell spread and proliferation. Moreover, the incorporation of graphene nanosheets endows Ca/Ag@P/G with great photothermal conversion effect, which is favorable to enhancing osteogenesis capability and synergistically killing/prohibiting bacteria/tumor cells. The multifunctional Ca/Ag@P/G composite has a promising prospect in the potential applications for infectious/tumorous bone repair applications. Abstract : In this study, a functional hard tissue implant consisting of an electrically conductive P/G nanocomposite with a CaCO3 and AgNPs mixture coating is developed electrophoretically. The modified composite exhibits the strong antibacterial ability and the enhanced proliferation of BMSCs. Electrophoretic deposition (EPD) allows the deposition of homogeneous and dense ceramic and organic/inorganic coatings on complex geometries and shapes.